The Rise of Europe and Colonialism In Muslim Countries In The Case of Egypt and India - Havis Aravik; Achmad Irwan Hamzani; Ahmad Tohir (Penerbit dan Percetakan, CV. Picmotiv, 2023)
This writing aims to explore the rise of Europe and Colonialism in Muslim countries, focusing on the cases of Egypt and India. The goal is to gain a deeper understanding of the European resurgence and Colonialism in Muslim countries such as Egypt and India, with the hope that it can serve as a valuable lesson to avoid repetition in the future. The method employed is qualitative research based on library research, where all data sources are obtained from books, journals, and other scholarly articles closely related to the discussed topic. All data is inventoried, content is analyzed, and then compiled into a report. The findings reveal that the occurrence of colonialism in Egypt and India is attributed to the poor conditions of the society in those regions, encompassing economic, political, social, and religious aspects.